EVALUASI KESESUAIAN LAHAN SAWAH BERIRIGASI DI DESA AIR HITAM KECAMATAN LIMA PULUH KABUPATEN BATUBARA - Frans Ferdinan; Jamilah Jamilah; Sarifuddin Sarifuddin (Universitas Sumatera Utara, 2013)
Land evaluation is the process of estimation of the potential of the land for a variety of alternative uses. Land evaluation involves conducting a survey or research shapes the landscape, nature and distribution of land, and the distribution of vegetation types and aspects of other land. This research aims to determine the level of suitability for irrigated rice in Air Hitam Village Lima Puluh District Batubara Regency. This research was conducted in Air Hitam Village Lima Puluh District Batubara Regency and Technology Laboratory of Agriculture Faculty in May 2011 - April 2012. This research uses the method of limits refers to the level of the limiting factors of land characteristics. The data observed in the field (the physical environment) and the data matched the results of laboratory analysis (matching) with the criteria of suitability class irrigated rice land. The results showed that the limiting factor on irrigated land is soil depth, soil texture, and base saturation. Soil depth and soil texture can not repaired while the base saturation can repaired with the addition of organic matter. Keywords: land suitability evaluation, irrigated rice